Measurements of Size and Electrical Charges Carried by Precipitation Particles During RELAMPAGO Field Campaign - Avila, Eldo Edgardo (2022)
The electrical charge carried by raindrops provides significant information about thunderstorm electrification mechanisms, since the charge acquired by hydrometeors is closely related to the microphysical processes that they undergo within clouds. Investigation of charges on raindrops was conducted during the Remote sensing of Electrification, Lightning, And Meso-scale/micro-scale Processes with Adaptive Ground Observations field campaign. A newly designed instrument was used to determine simultaneously the fall velocity and charge for precipitating particles. Hydrometeor size and charge were measured in Córdoba city, Argentina, during electrified storms. Temporal series of size-charge of single raindrops were recorded for two storms, which were also monitored with a Parsivel disdrometer and Lightning Mapping Array. The results show that the magnitude of the electric charges range between 1 and 50 pC and more than 90% of the charges are mainly carried by raindrops >1 mm, even though most of the raindrops are smaller than 1 mm. Furthermore, the measurement series show charged hydrometeors of both signs all the time. A correlation between the sizes and the charges carried by the raindrops was found in both storms.